PERDAMAIAN SOSIAL DALAM AL-QUR’AN: RELEVANSI AYAT-AYAT KONFLIK UNTUK RESOLUSI KONTEMPORER - Nurusshobah, Nurusshobah; Ismail, Hasan; Harfi, Muhammad; Wahid, Ilham Dhya'ul (UIN ANTASARI BANJARMASIN, 2025)
This paper investigates the Qur’anic approach to fostering social peace by thematically analyzing verses related to conflict and its resolution. It examines the underlying drivers of social tension such as injustice, intolerance, and social disparity while emphasizing Qur’anic ethics, including reconciliation (ṣulḥ), balanced conduct (tawassuṭ), and respectful engagement (mu‘āsharah). Using qualitative methods through literature-based analysis, the study draws from both classical and contemporary tafsir to uncover how these verses can inform current social dynamics. The results reveal that the Qur’an promotes a moral framework for resolving conflict, grounded in equity, mercy, and mutual respect. These insights remain highly relevant in addressing present-day societal and interfaith disputes. Academically, this research enriches Qur’anic studies with a thematic-exegetical contribution; practically, it offers value-based strategies to guide peaceful coexistence in diverse communities.